Opioid analgesia on the battlefield: a retrospective review of data from Operation HERRICK. Issue 5 (6th April 2018) - Lewis, Pip; Wright, C; Hooper, C
Abstract : Background: Acute pain secondary to trauma is commonly encountered on the battlefield. The use of morphine to manage pain during combat has been well established since the 19th century. Despite this, there is relatively little research on analgesia use in this environment. This study aims to review the use and complications of morphine and other opioids during Operation HERRICK. Methods: A database search of the Joint Theatre Trauma Registry was completed looking for all incidences of morphine, fentanyl or naloxone use from February 2007 to September 2014. Microsoft Excel was used to analyse the results. Results: Opioid analgesia was administered to 5801 casualties. Morphine was administered 6742 times to 3808 patients. Fentanyl was administered 9672 times to 4318 patients. Naloxone was used 18 times on 14 patients, giving a complication rate of 0.24%. Opioid doses prior to naloxone administration range from 0 to 72 mg of morphine and from 0 to 100 mcg of fentanyl. Four casualties (two local civilians and two coalition forces) received naloxone despite no recorded opioids being administered. Opium abuse was prevalent among the local population in Afghanistan, and this could explain the rationale behind two local national casualties receiving naloxone without any documented opioids being given. Conclusion: The use of opioids in a battlefield environment is extremely safe. Complication rates are similar to previously published data which is reassuring. The efficacy of different opioids was not covered by this study, and further analysis is required, particularly following the introduction of oral transmucosal fentanyl citrate and the availability of novel non-opioid analgesics.